Enhanced Solar Water Splitting by Swift Charge Separation in Au/FeOOH Sandwiched Single‐Crystalline Fe2O3 Nanoflake Photoelectrodes. Issue 13 (8th June 2017) - Wang, Lei; Nguyen, Nhat Truong; Zhang, Yajun; Bi, Yingpu; Schmuki, Patrik
Abstract: In this work, single crystalline α‐Fe2 O3 nanoflakes (NFs) are formed in a highly dense array by Au seeding of a Fe substrate by a thermal oxidation technique. The NFs are conformally decorated with a thin FeOOH cocatalyst layer. Photoelectrochemical (PEC) measurements show that this photoanode, incorporating α‐Fe2 O3 /FeOOH NFs rooted on the Au/Fe structure, exhibits significantly enhanced PEC water oxidation performance compared to the plain α‐Fe2 O3 nanostructure on the Fe substrate. The α‐Fe2 O3 /FeOOH NFs on Au/Fe photoanode yields a photocurrent density of 3.1 mA cm −2 at 1.5 VRHE, and a remarkably low onset potential of 0.5–0.6 VRHE in 1 m KOH under AM 1.5G (100 mW cm −2 ) simulated sunlight illumination. The enhancement in PEC performance can be attributed to a synergistic effect of the FeOOH top decoration and the Au underlayer, whereby FeOOH facilitates hole transfer at the interface of electrode/electrolyte and the Au layer provides a sink for the electron transport to the back contact. This results in a drastically improved charge‐separation efficiency in the single crystalline α‐Fe2 O3 NF photoanode. Abstract : Flake news : FeOOH and Au layers on single‐crystalline α‐Fe2 O3 nanoflake photoanodes display a synergistic effect in water splitting. Au seeding provides nucleation centers to grow high‐density hematite nanoflake arrays on Fe substrate. Additional FeOOH decoration facilitates hole transfer at the electrode/electrolyte interface, while the remaining Au underlayer provides a sink for electron transport to the back contact, leading to drastically improved charge‐separation efficiency.